Strengthening Posyandu Cadres’ Capacity in Close Contact Tracing for Pulmonary Tuberculosis at Pamolokan Health Center - Hannan, Mujib; Permatasari, Dian; Suprayitno, Emdat (Help: Journal of Community Service, 2025)
Pulmonary Tuberculosis (TB) remains the infectious disease with the highest mortality rate in Sumenep Regency, while the discovery of new cases at Pamolokan Health Center in 2025 reached only 52.6% of the national target of 90%. One key factor is the limited capacity of Posyandu cadres, who serve as the frontline in community-based health services, particularly in conducting close contact tracing. Strengthening their competence is essential to improve early TB case detection and reduce household transmission. This community service program applied a Participatory Action Research (PAR) approach consisting of preparation, training, field mentoring, and evaluation. Twenty-five Posyandu cadres participated in interactive lectures, group discussions, case-based simulations, and on-the-job mentoring. Knowledge improvement was measured using pre-tests and post-tests, while skills were assessed through direct observation checklists during simulated and real field visits. The program significantly increased cadres’ knowledge, with average scores rising from 55.6% (pre-test) to 86.4% (post-test). The greatest improvement occurred in understanding close contact criteria (45%) and reporting procedures (40%). Skills also improved, with 92% of cadres demonstrating confident and structured communication during field visits and 88% successfully completing contact tracing forms accurately. Over three weeks of mentoring, cadres identified 42 close contacts from 15 TB patient households, with 38 (90.5%) agreeing to undergo examination at the health center. The combination of interactive training and on-the-job mentoring proved effective in strengthening cadres’ knowledge and practical abilities. Their social proximity to families helped reduce stigma-related barriers and improved cooperation during home visits. This approach also promoted sustainability, as cadres gained confidence to continue tracing activities with minimal supervision.